High-airtightness low-haze environment-friendly cover plate glass as well as preparation method and application thereof

By adjusting the composition and content of various oxides in the cover glass, high-air tightness and low-haze environmentally friendly cover glass is prepared, which solves the problem of lid glass being easily corroded in the wet and oxidized environment in the prior art, and achieves higher air tightness, strength and environmental protection performance.

CN119822638AActive Publication Date: 2025-04-15CNBM PHOTONICS TECH CO LTD

Patent Information

Application Number
CN202510010768.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-03
Publication Date
2025-04-15
Estimated Expiration
2045-01-03

AI Technical Summary

Technical Problem

Existing cover glasses are prone to oxidation and corrosion in wet and oxidized environments, resulting in a shortened service life. At the same time, their airtightness and corrosion resistance are insufficient, which affects the performance of digital products.

Method used

By reasonably adjusting the composition and content of SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, Ag2O, In2O3 and CeO2, high-air-tightness and low-haze environmentally friendly cover glass is prepared to improve its air-tightness, transmittance, strength and environmental protection performance.

Benefits of technology

The excellent comprehensive performance of cover glass in haze, strength, water vapor transmission, optical transmission and environmental protection is achieved, extends its service life, and is harmless to the human body and the environment during the melting process.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119822638A_ABST
    Figure CN119822638A_ABST
Patent Text Reader

Abstract

The invention relates to a special glass material, in particular to high-airtightness low-haze environment-friendly cover plate glass as well as a preparation method and application thereof. The high-temperature-resistant glass is prepared from the following components in parts by weight: 53.0 to 62.0 parts of SiO2, 9.0 to 15.0 parts of Al2O3, 0.1 to 2.0 parts of CaO, 4.0 to 8.0 parts of MgO, 3.0 to 7.0 parts of K2O, 9.0 to 15.0 parts of Na2O, 0 to 2.0 parts of Li2O, 0.5 to 2.0 parts of ZrO2, 2.0 to 6.0 parts of B2O3, 0 to 3.0 parts of Bi2O3, 0 to 2.0 parts of Ag2O, 0 to 3.0 parts of In2O3 and 0.1 to 1.0 part of CeO2. The cover plate glass provided by the invention not only has good performances in the aspects of air tightness, transmittance, haze, strength, chemical stability and environmental protection property, but also can be reduced to generate a black light absorption layer, and has good processability.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a special glass material, and in particular to a high-airtightness, low-fog, environmentally friendly cover glass, and a preparation method and application thereof. Background Art

[0002] Cover Lens or Cover Glass, also known as window protection screen, is mainly used in the front screen, back cover and other positions. The OLED and many sensitive electronic components connected behind the cover glass require a dry working environment. Long-term exposure to a humid and oxidizing environment can easily cause oxidation corrosion, greatly shortening the service life of the touch module. The cover glass, as a protective barrier for the display touch module, is in direct contact with the human body, and sweat is particularly corrosive to the display touch module and electronic components. The airtightness of the glass is an important standard for the constant glass to isolate water vapor and oxygen. Therefore, the airtightness and corrosion resistance of the cover glass directly affect the service life of mobile phone digital products.

[0003] On the other hand, cover glass requires high strength and scratch resistance, which often requires the introduction of a large amount of high-viscosity oxides into the glass. In order to reduce the difficulty of glass clarification during the production process, relatively fusible nitrates are often used as raw materials, and clarifiers such as As2O3 and Sb2O3 are also used in combination to accelerate the discharge of bubbles in the glass. However, clarifiers such as As2O3 and Sb2O3 will produce heavy metals such as arsenic and antimony during the glass melting process, which are seriously harmful to the human body. At the same time, nitrates will also form nitrogen oxides (NO X ), causing pollution to the environment. Summary of the invention

[0004] In order to address the deficiencies in the prior art, the purpose of the present invention is to provide a highly airtight, low-haze, environmentally friendly cover glass and a preparation method and application thereof. The cover glass provided by the present invention has good performance, not only in terms of airtightness, transmittance, haze, strength and environmental protection, but also the glass can produce a black light-eliminating layer under a reducing atmosphere, and also has good chemical stability and good processing performance, and has broad application prospects.

[0005] In order to achieve the above-mentioned purpose, the high-airtightness, low-fog, environmentally friendly cover glass material provided by the present invention contains SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, Ag2O, In2O3, and CeO2, and achieves excellent comprehensive performance, including haze, strength, water vapor transmittance, optical transmittance, and environmental protection, by controlling the composition and content thereof. The specific technical scheme is as follows.

[0006] In a first aspect, a highly airtight, low-fog, environmentally friendly cover glass is composed of the following components, in parts by weight: 53.0 to 62.0 parts of SiO2, 9.0 to 15.0 parts of Al2O3, 0.1 to 2.0 parts of CaO, 4.0 to 8.0 parts of MgO, 3.0 to 7.0 parts of K2O, 9.0 to 15.0 parts of Na2O, 0 to 2.0 parts of Li2O, 0.5 to 2.0 parts of ZrO2, 2.0 to 6.0 parts of B2O3, 0 to 3.0 parts of Bi2O3, 0 to 2.0 parts of Ag2O, 0 to 3.0 parts of In2O3, and 0.1 to 1.0 parts of CeO2; wherein the weight percentage of at most one component among Bi2O3, Ag2O, and In2O3 is 0.

[0007] The sum of the weight parts of the components in the present invention is 100 parts.

[0008] In the above-mentioned cover glass system, the present invention can reduce the viscosity of molten glass and the difficulty of glass molding by controlling the contents of CaO, K2O, Na2O, Bi2O3 and B2O3; by controlling the contents of SiO2, Al2O3, Na2O, K2O, Bi2O3 and Ag2O, the tendency of glass crystallization can be reduced and the permeability of the glass after molding can be improved. By controlling the contents of SiO2, Al2O3, CaO, MgO and Ag2O, the chemical stability and air tightness of the glass can be improved, the corrosion resistance of the glass in complex environments can be improved, and the service life of the glass can be extended. By controlling the contents of Al2O3, Ag2O, MgO, ZrO2 and Ag2O, the strength of the glass can be improved, and the scratch resistance and drop resistance of the glass can be enhanced; in addition, the presence of Na2O and K2O gives the glass the ability to be chemically strengthened. At the same time, by controlling the content and proportion of reducing substances Bi2O3, Ag2O, In2O3 and alkali metal compounds K2O and Na2O, the water vapor permeability, bending strength and optical properties can be further adjusted.

[0009] In the above-mentioned glass system of the present invention, the integrated effect of SiO2, CaO, Al2O3, B2O3 and MgO jointly improves the thermal stability and chemical stability of the glass. The synergistic effect of CaO, Al2O3, B2O3 and MgO adjusts the thermal expansion coefficient and enhances the chemical stability. The addition of MgO further improves the corrosion resistance of the glass in complex environments and prolongs its service life. The introduction of Al2O3, MgO, B2O3, Ag2O and Bi2O3 improves the optical quality and enhances the optical transmittance of the glass material. The combined effect of Na2O, Bi2O3, B2O3 and CeO2 reduces the difficulty of glass clarification and reduces defects such as bubbles in the glass melting process.

[0010] In summary, the high-airtightness, low-fog, environmentally friendly cover glass provided by the present invention contains SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, Ag2O, In2O3, and CeO2 at the same time. By precisely controlling the contents of SiO2, Al2O3, CaO, MgO, K2O, Na2O, Li2O, ZrO2, B2O3, Bi2O3, Ag2O, In2O3, and CeO2, the glass has excellent comprehensive performance in terms of haze, strength, water vapor transmittance, optical transmittance, environmental protection, and thickness of the reduced blackened layer.

[0011] The present invention has been experimentally shown that the cover glass provided by the present invention has a water vapor transmission rate of ≤8×10 -9 g / m 2 ·d. Haze ≤ 0.39%, bending strength ≥ 129MPa, maximum optical transmittance of 2mm glass sample within the wavelength range of 400-1000nm is not less than 90.0% and other excellent comprehensive properties.

[0012] In a second aspect, a method for preparing the above-mentioned high-airtightness, low-fog, environmentally friendly cover glass is provided, which comprises uniformly mixing the raw materials according to the proportion of each component, and then sequentially melting, stirring, clarifying, and molding the mixed mixture.

[0013] In a third aspect, an application of the above-mentioned high-airtightness, low-fog, environmentally friendly cover glass in the preparation of a screen substrate.

[0014] In a fourth aspect, a use of the above-mentioned high-airtightness, low-fog, environmentally friendly glass cover plate in the preparation of a digital product cover plate.

[0015] The beneficial effects of the present invention are:

[0016] 1. The high-airtightness, low-fog, environmentally friendly cover glass provided by the present invention has the following excellent properties by adjusting the composition and content of each component: water vapor transmission rate ≤8×10 -9 g / m 2 ·d, haze ≤ 0.39%, bending strength ≥ 129MPa, maximum optical transmittance of 2mm glass sample in the wavelength range of 400-1000nm ≥ 90.0%; meanwhile, the cover glass is harmless to human body and environment during the melting process.

[0017] 2. The high-airtightness, low-fog, environmentally friendly cover glass provided by the present invention also has the following properties: acid resistance stability and moisture resistance stability are level 1, and the mechanical properties and processing properties are good, so it can be used as the main material for various digital product covers. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.

[0019] Figure 1 It is a comparative curve chart of the transmittance of the 2 mm thick glass products of Comparative Example 1 and Example 1 in the wavelength range of 400 to 1000 nm.

[0020] Figure 2 It is a comparison chart of the bending strength (a), haze (b) and water vapor transmission rate (c) of the glass materials of Examples 1 to 9 and Comparative Examples 1 to 5. DETAILED DESCRIPTION

[0021] It should be noted that the following detailed descriptions are exemplary and are intended to provide further explanation of the present invention. Unless otherwise specified, all technical and scientific terms used herein have the same meanings as those commonly understood by those skilled in the art to which the present invention belongs.

[0022] It should be noted that the terms used herein are only for describing specific embodiments and are not intended to limit exemplary embodiments according to the present invention. As used herein, unless the context clearly indicates otherwise, the singular form is also intended to include the plural form. In addition, it should be understood that when the terms "comprising" and / or "including" are used in this specification, it indicates the presence of features, steps, operations, devices, components and / or combinations thereof.

[0023] In view of the fact that the air tightness and corrosion resistance of the existing substrate glass cannot meet the increase in the service life of digital products, the present invention proposes a high-air tightness, low-fog, environmentally friendly cover glass and a preparation method and application thereof.

[0024] A typical embodiment of the present invention provides a high-airtightness, low-fog, environmentally friendly cover glass, which is composed of the following components, in parts by weight: 53.0 to 62.0 parts of SiO2, 9.0 to 15.0 parts of Al2O3, 0.1 to 2.0 parts of CaO, 4.0 to 8.0 parts of MgO, 3.0 to 7.0 parts of K2O, 9.0 to 15.0 parts of Na2O, 0 to 2.0 parts of Li2O, 0.5 to 2.0 parts of ZrO2, 2.0 to 6.0 parts of B2O3, 0 to 3.0 parts of Bi2O3, 0 to 2.0 parts of Ag2O, 0 to 3.0 parts of In2O3, and 0.1 to 1.0 parts of CeO2; wherein the weight percentage of at most one component among Bi2O3, Ag2O, and In2O3 is 0.

[0025] In the present invention, SiO2 is a glass-forming oxide. As the main constituent of glass, it provides the basic framework of the structure and gives the glass good chemical stability and mechanical strength. The appropriate SiO2 content can reduce the thermal expansion coefficient of the glass and improve the thermal stability, chemical stability, softening temperature, heat resistance, hardness and mechanical strength of the glass. Too high a content of SiO2 may lead to an increase in the melting point and difficulty in processing; too low a content of SiO2 may weaken the chemical stability and mechanical strength. SiO2 is preferably 53.0 to 60.0 parts, 53.0 to 58.0 parts, 55.0 to 58.0 parts, 56.0 to 58.0 parts, 56.5 to 57.5 parts, etc.

[0026] Al2O3 is an essential component for improving the chemical stability of glass, which can reduce the tendency of glass crystallization. It is also a component for improving the hardness and mechanical strength of glass and increasing the tensile elastic modulus. In the glass network structure, alumina is a network intermediate oxide, between the network generator and the network exogenous body. Al2O3 is preferably 9.0-9.5 parts, 11.0-15.0 parts, 11.0-14.0 parts, 12.0-14.0 parts, 12.5-13.5 parts, etc.

[0027] In the present invention, the introduction of CaO can increase the chemical stability and mechanical strength of the glass, but when the amount introduced is too much, the glass is prone to crystallization and the thermal stability of the glass is reduced. At the same time, CaO can reduce the viscosity of the glass at high temperature, which is conducive to clarification; the introduction of MgO can improve the thermal stability of the glass, and the introduction of MgO will reduce the thermal expansion coefficient of the glass, but too much MgO will increase the viscosity of the glass, resulting in difficulty in glass molding. MgO and CaO jointly enhance the mechanical strength and chemical durability of the glass in the present invention. The addition of MgO is particularly helpful to reduce the increase in the thermal expansion coefficient caused by CaO. CaO is preferably 0.4-2.0 parts, 0.7-2.0 parts, 0.7-1.3 parts, 1.7-2.0 parts, etc. MgO is preferably 4.9-8.0 parts, 5.0-8.0 parts, 5.0-7.0 parts, 5.5-6.5 parts, etc.

[0028] In the present invention, K2O and Na2O are network external oxides of glass. Alkali metal ions are easy to move and diffuse in the glass body, which can reduce the viscosity of glass during high-temperature melting and make the glass easy to melt. They are good fluxing agents, but the amount introduced should not be too much. Excessive introduction will increase the thermal expansion coefficient of the glass and reduce the chemical stability, thermal stability and mechanical strength of the glass. In addition, K2O can improve the gloss of the glass, reduce the haze on the surface of the glass, and improve the transmittance of the glass after molding. K2O is preferably 3.5-6.5 parts, 3.5-6.0 parts, 4.0-6.0 parts, 4.5-5.5 parts, etc. Na2O is preferably 9.2-15.0 parts, 9.0-14.0 parts, 9.0-14.0 parts, 10.0-12.0 parts, 11.0-12.0 parts, etc.

[0029] In the present invention, Li2O can combine with oxygen atoms in the glass network to form Li-O bonds, which helps to strengthen the network structure of the glass and improve the physical properties of the glass. Moreover, the introduction of Li2O in the present invention can reduce the tendency of crystal formation during the cooling and solidification of the glass, help maintain the amorphous state of the glass, and can improve the optical transparency of the glass, thereby making the glass more transparent, improving the optical transmittance of the glass, and reducing the haze of the glass. However, it should be noted that the amount of Li2O used needs to be precisely controlled. Excessive Li2O will reduce the chemical stability of the glass and may cause the glass to be more susceptible to crystallization and phase separation. Li2O is preferably 0.1 to 2.0 parts, 0 to 1.0 parts, 0 to 0.9 parts, 0.1 to 0.9 parts, 0.3 to 0.7 parts, etc.

[0030] In the present invention, ZrO2 is a glass intermediate oxide, which has the effect of improving chemical stability and preventing the exposure of alkali metal and alkaline earth metal ions. It is also an important component for improving the tensile elastic modulus, and is very helpful for improving the hardness of glass after chemical strengthening. ZrO2 is preferably 0.5 to 1.3 parts, 1.3 to 2.0 parts, 0.7 to 1.3 parts, etc.

[0031] In the present invention, B2O3 is also a glass-forming oxide, which has boron oxide triangles [BO3] and boron oxide tetrahedrons [BO4] as structural units, and together with silicate tetrahedrons in borosilicate glass, forms a structural network. B2O3 can reduce the viscosity of glass at high temperatures and increase the viscosity of glass at low temperatures, so the glass with a higher B2O3 content has a wider forming temperature range. B2O3 also acts as a flux, accelerating the dissolution and clarification of the glass. However, when the amount of B2O3 added is too high, due to the increase in boron oxide triangles, the expansion coefficient of the glass increases instead, boron anomaly occurs, and the chemical stability of the glass is reduced. B2O3 is preferably 2.0 to 5.5 parts, 2.0 to 5.0 parts, 2.0 to 4.5 parts, 2.0 to 4.0 parts, 2.0 to 3.5 parts, 2.5 to 3.5 parts, 2.8 to 3.2 parts, etc.

[0032] In the present invention, the synergistic effect of two or three of Bi2O3, Ag2O and In2O3 can improve the light absorption rate of glass after reduction and blackening. The addition of Bi2O3 can improve the refractive index and dispersion capacity. Bi2O3 also helps to improve the thermal stability of glass and enhance the light absorption capacity. At the same time, since the Bi element (usually introduced as Bi2O3 or Bi(NO3)3) can be reduced to black under a high-temperature hydrogen atmosphere, this property can be used to optimize the stray light absorption effect. However, the introduction of Bi2O3 requires precise control. Excessive addition of Bi2O3 may lead to a significant reduction in the chemical stability of the glass, especially when reacting with reducing gases, its stability problem is more prominent. In addition, high concentrations of Bi2O3 may cause serious erosion to the melting container during the glass melting process, which limits its scope of application in glass production. In addition, too much Bi2O3 may also promote glass crystallization, affecting its transparency and optical uniformity. On the contrary, insufficient Bi2O3 content makes it difficult to improve optical properties. The introduction of Ag2O can improve the optical properties of glass. Ag2O has good absorption and reflection properties, so it can effectively block the penetration of ultraviolet rays and visible light, and improve the light transmittance and light-shielding properties of glass. Secondly, it can improve the chemical stability and mechanical strength of glass. Ag2O can form a composite glass structure and a crystal hardening layer with other glass additives to improve the corrosion resistance, hardness and toughness of glass materials, thereby enhancing their mechanical strength and impact resistance. In2O3 can improve the thermal conductivity and mechanical properties of glass materials. When the indium content is low, the thermal stability and heat resistance of glass can be effectively improved; and when the indium content increases, the density and refractive index of glass will also increase. However, excessive In2O3 content can also easily cause serious discoloration of glass. Bi2O3 is preferably 0.1 to 3.0 parts, 0.1 to 2.5 parts, 0.1 to 2.0 parts, 0.1 to 1.5 parts, 0.1 to 1.0 parts, 0.1 to 0.9 parts, 0.3 to 0.7 parts, etc. Ag2O is preferably 0.1-2.0 parts, 0.1-1.5 parts, 0.1-1.0 parts, 0.1-0.9 parts, 0.3-0.7 parts, etc. In2O3 is preferably 0.1-3.0 parts, 0.1-2.5 parts, 0.1-2.0 parts, 0.1-1.5 parts, 0.1-1.0 parts, 0.1-0.9 parts, 0.3-0.7 parts, etc.

[0033] Cerium oxide is an environmentally friendly clarifier. Its clarification mechanism is that cerium oxide is an oxide with variable valence. Cerium oxide decomposes oxygen at high temperature. The more oxygen that can be separated from its chemical bonds for every 1°C increase, the better the clarification effect. The solubility of oxygen decreases with increasing temperature, resulting in a clarification effect. No toxic gas is generated during the clarification process. CeO2 is preferably 0.1 to 0.8 parts, 0.1 to 0.7 parts, 0.1 to 0.6 parts, 0.1 to 0.5 parts, 0.1 to 0.4 parts, 0.1 to 0.3 parts, 0.3 to 0.8 parts, 0.4 to 0.8 parts, 0.4 to 0.7 parts, 0.5 to 0.7 parts, etc.

[0034] In some embodiments, the weight fraction of Na2O is greater than seven-ninths of the weight fraction of K2O. Studies have shown that glass with this component condition has better performance.

[0035] In some embodiments, the weight fraction of B2O3 is less than two-thirds of the weight fraction of Al2O3. Studies have shown that glass with this composition has better performance.

[0036] In some embodiments, the sum of the weight parts of Bi2O3, Ag2O, and In2O3 is greater than 1 part, preferably 1.1 to 5 parts, more preferably 1.1 to 4 parts, and even more preferably 1.1 to 2 parts. Studies have shown that the glass performance under this composition condition is better.

[0037] In some embodiments, the water vapor transmission rate is ≤8×10 -9 g / m 2 ·d, preferably (2 to 8)×10 -9 g / m 2 ·d, preferably (2 to 6)×10 -9 g / m 2 ·d, preferably (2 to 5)×10 -9 g / m 2 ·d, preferably (2 to 3)×10 -9 g / m 2 ·d.

[0038] In some embodiments, the haze is ≤ 0.39%, preferably 0.18-0.39%, preferably 0.18-0.32%, preferably 0.18-0.26%, preferably 0.18-0.24%, preferably 0.18-0.20%, preferably 0.18-0.19%.

[0039] In some embodiments, the flexural strength is ≥ 129 MPa, preferably 129-141 MPa, preferably 132-141 MPa, and preferably 139-141 MPa.

[0040] In some embodiments, the maximum optical transmittance of a 2 mm glass sample in the wavelength range of 400 to 1000 nm is ≥ 90.0%, preferably 90.0 to 91.8%, and preferably 91.0 to 91.8%.

[0041] Another embodiment of the present invention provides a method for preparing the above-mentioned high-airtightness, low-fog, environmentally friendly cover glass, which comprises uniformly mixing the raw materials according to the proportion of each component, and then sequentially melting, stirring, clarifying, and molding the mixed mixture to obtain the cover glass.

[0042] In some embodiments, the melting temperature is 1500-1580° C. Specifically, the melting time is 8-30 hours. Under this melting time condition, it is helpful to clarify the glass liquid.

[0043] When the uniformity of the liquid is low, the liquid is prone to stratification or agglomeration, making it difficult to melt and homogenize the glass, and even causing streaks or stone defects in severe cases. In some embodiments, the stirring speed is 10 to 20 r / min, and the stirring time is 3 to 12 hours. This stirring condition is conducive to the uniformity of the liquid.

[0044] In some embodiments, the molding temperature is 1350-1400° C., and the molding time is 5-25 minutes. Under such molding conditions, the molding speed of the glass can be increased, and the generation of secondary bubbles and impurities can be avoided.

[0045] A third embodiment of the present invention provides a use of the above-mentioned high-airtightness, low-fog, environmentally friendly cover glass in the preparation of a screen substrate.

[0046] A fourth embodiment of the present invention provides an application of the above-mentioned high-airtightness, low-fog, environmentally friendly cover glass in the preparation of a cover for a digital product.

[0047] In some embodiments, the cover glass includes a light absorption region, and the maximum optical transmittance of the light absorption region is ≤2.9%, preferably 1.3-2.9%, and preferably 1.3-2.0%.

[0048] In one or more embodiments, the light absorption zone is obtained by continuing the blackening treatment of the high-airtightness, low-fog, environmentally friendly cover glass. Specifically, the blackening treatment is carried out in a reducing atmosphere, the blackening treatment time is 4000 to 16000 minutes, the pressure of the reducing atmosphere is 0.01 to 0.5 MPa, and the temperature is 450 to 620°C. For example, under reducing atmosphere conditions, the pressure of the reducing atmosphere is 0.01 MPa, the blackening temperature is 600°C, and the blackening time is 10000 minutes. More specifically, the reducing atmosphere is a hydrogen atmosphere, and there are multiple cycles of inflation and deflation during the entire reduction process, and a cycle period is 160 to 300 minutes.

[0049] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in combination with specific embodiments and comparative examples.

[0050] The performance parameters in the following embodiments are measured according to the following methods:

[0051] The thermal expansion coefficient α of the glass sample was tested using the DIL 402 expansion coefficient tester produced by NETZSCH, Germany. Sample preparation: The glass sample was polished into a cylindrical glass strip of Φ6×50mm, and the two end surfaces were parallel. The heating rate was set to 5℃ / min, and the data acquisition cycle was 20ms. Refer to GB / T7962.16-2010.

[0052] The softening point temperature of the glass sample is tested using the Model PPV-1000 / 1200 plate viscometer produced by Orton. Sample preparation: The glass sample is polished into a cylindrical glass strip of Φ6×6mm, and the two end faces are parallel. The sample is placed between the top and bottom discs, which are made of heat-resistant metal alloys with a diameter of 44mm and a thickness of 6mm. The top metal disc is connected to the bottom of the probe rod. Two very thin platinum films (40mm in diameter and 0.001 inches thick) are placed between the sample and the top and bottom discs to facilitate sampling and sample placement. Refer to ASTM C-1351M.

[0053] The transmittance test was carried out using a UV-visible-infrared spectrophotometer.

[0054] After the surface of the polished glass sample is corroded by the test medium with acidity of pH2.9, pH4.6, and pH6.0, observe the time when the purple-blue interference color appears on the glass surface, or the surface becomes mottled or falls off under an incandescent lamp. The acid resistance stability of colorless optical glass is classified in descending order according to the length of time. Refer to GB / T 7962.14-2010.

[0055] Polished glass samples are kept at a constant temperature and humidity of 50°C and 85% relative humidity for 20 hours, and the moisture resistance stability of colorless optical glass is classified in descending order by comparing the turbidity values ​​with those of standard samples H (BaK7) and H (ZK9). Refer to GB / T7962.15-2010.

[0056] The haze of glass samples was tested using the Qunlong CS series haze tester. Sample preparation: The glass samples were ground and polished into Φ32×20mm circular glass sheets. The spectral response was the CIE spectral function Y / V(λ), with a wavelength range of 400-700nm, a wavelength interval of 10nm, and a resolution of 0.01 units. Refer to GB / T24010.

[0057] The bending strength of glass samples is tested using the three-point bending method. The glass sample is processed into the required size for the test, and then the glass sample is placed between two supporting points and a fixed load is applied perpendicular to the center of the sample. Then, by applying different bending moments, the bending stress and strain of the glass are measured under different conditions. Finally, the bending strength of the glass is determined. Refer to GB / T 37781-2019.

[0058] Example 1

[0059] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figures 1-2 .

[0060] The preparation method of the high-airtightness, low-fog, environmentally friendly cover glass is as follows: quartz sand, aluminum hydroxide, calcium carbonate, basic magnesium carbonate, potassium carbonate, sodium carbonate, lithium carbonate, zirconium oxide, bismuth oxide, silver phosphate, indium oxide, and cerium oxide are used as raw materials, and after being fully mixed, they are melted at 1540°C for 12 hours, mechanically stirred (15r / min, 4 hours), assisted with high-temperature clarification, and pressed at 1380°C (molding time is 5 minutes) to obtain glass blanks. The glass blanks are placed in an annealing furnace heated to 580°C in advance for annealing to eliminate the stress in the glass to meet the requirements of later cold processing.

[0061] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set, the blackening temperature is 600°C, the reducing gas hydrogen pressure is 0.01MPa, and the blackening time is 10000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0062] Example 2

[0063] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0064] In the preparation method of high-airtightness, low-fog, environmentally friendly cover glass, the melting temperature is 1550°C, the melting time is 16h; mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, the molding time is 15min, and the other preparation steps and parameters are the same as Example 1.

[0065] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 620°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 10,000 minutes. After the blackening process is completed, a stray light absorption layer is formed on the glass surface.

[0066] Example 3

[0067] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0068] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1580°C, the melting time is 30h, mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0069] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 450°C, a reducing gas hydrogen pressure of 0.3MPa, and a blackening time of 4000min. After the blackening process is completed, a stray light absorption layer is formed on the glass surface.

[0070] Example 4

[0071] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0072] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 20h, mechanical stirring (10r / min, 14h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0073] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set with a blackening temperature of 500°C, a reducing gas hydrogen pressure of 0.4MPa, and a blackening time of 6000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0074] Example 5

[0075] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0076] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1500°C and the melting time is 25h; mechanical stirring (20r / min, 14h), the molding temperature is 1380°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0077] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 530°C, a reducing gas hydrogen pressure of 0.5MPa, and a blackening time of 12000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0078] Example 6

[0079] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0080] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 30h, mechanical stirring (20r / min, 12h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0081] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 620°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 16000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0082] Example 7

[0083] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0084] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1550°C, the melting time is 30h, mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 25min. The other preparation steps and parameters are the same as those in Example 1.

[0085] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 600°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 13000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0086] Example 8

[0087] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0088] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1550°C, the melting time is 30h, mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 20min. The other preparation steps and parameters are the same as those in Example 1.

[0089] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 610°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 8000min. After the blackening process is completed, a stray light absorption layer is formed on the glass surface.

[0090] Example 9

[0091] The components of the high-airtightness, low-fog, environmentally friendly cover glass of this embodiment, the weight percentage of each component, and the physical properties of the prepared glass are shown in Table 1, Table 3, Figure 2 .

[0092] In the preparation method of the high-airtightness, low-fog, environmentally friendly cover glass in this embodiment, the melting temperature is 1560°C, the melting time is 30h, mechanical stirring (20r / min, 14h), the molding temperature is 1400°C, and the molding time is 20min. The other preparation steps and parameters are the same as those in Example 1.

[0093] After annealing, the glass blank is processed into a certain size and placed in a blackening reduction furnace. The blackening program is set to a blackening temperature of 590°C, a reducing gas hydrogen pressure of 0.2MPa, and a blackening time of 9000min. After the blackening treatment is completed, a stray light absorption layer is formed on the glass surface.

[0094] Comparative Examples 1 to 5

[0095] The components of the glasses of Comparative Examples 1 to 5, the weight percentage of each component, and the physical properties of the glasses obtained are shown in Tables 2, 4, Figures 1-2 .

[0096] The preparation steps, blackening reduction steps and parameters of the glass in Comparative Examples 1 to 5 are the same as those in Example 1.

[0097] Table 1 Components and contents of the environmentally friendly cover glass of Examples 1 to 9 of the present invention

[0098]

[0099]

[0100] Table 2 Components and contents of glass in comparative examples 1 to 5 of the present invention

[0101]

[0102]

[0103] Table 3 Performance test results of glass samples of Examples 1 to 9

[0104]

[0105]

[0106] Table 4 Performance test results of glass samples of Comparative Examples 1 to 5

[0107]

[0108]

[0109] In Tables 3 and 4, the samples with the test item "maximum optical transmittance after reduction / % (350-1000 nm)" are glass samples after reduction blackening treatment, and the samples with other test items are glass samples before reduction blackening treatment.

[0110] By reasonably adding corresponding components and controlling the ratio of each component in the raw materials, the haze, strength, water vapor permeability, optical transmittance and environmental performance of the glass are better in Examples 1 to 9. As can be seen from Table 3, the optical transmittance of the high-airtightness, low-haze and environmentally friendly cover glass prepared in Examples 1 to 9 of the present invention is as follows: within the wavelength range of 400-1000nm, the maximum transmittance is 92.8%. The comprehensive performance is better than the glass involved in Comparative Examples 1 to 5, and it has good acid / moisture resistance stability, and can maintain the stability of the internal structure of the glass for a long time.

[0111] As can be seen from the above, the high-airtightness, low-fog, environmentally friendly cover glass provided by Examples 1 to 9 of the present invention has excellent optical transmittance, low haze, high bending strength, low water vapor permeability, and good processing performance. This is because Examples 1 to 9 of the present invention adjust the proportion of each component raw material in the preparation of the high-airtightness, low-fog, environmentally friendly substrate glass, and set a suitable stirring speed and time. Therefore, the high-airtightness, low-fog, environmentally friendly cover glass of the present invention has high optical transmittance, high bending strength, low haze and water vapor permeability, and has broad application prospects.

[0112] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.

Claims

1. A high-airtightness, low-fog, environmentally friendly cover glass, characterized in that: The invention is composed of the following components in parts by weight: 53.0 to 62.0 parts of SiO2, 9.0 to 15.0 parts of Al2O3, 0.1 to 2.0 parts of CaO, 4.0 to 8.0 parts of MgO, 3.0 to 7.0 parts of K2O, 9.0 to 15.0 parts of Na2O, 0 to 2.0 parts of Li2O, 0.5 to 2.0 parts of ZrO2, 2.0 to 6.0 parts of B2O3, 0 to 3.0 parts of Bi2O3, 0 to 2.0 parts of Ag2O, 0 to 3.0 parts of In2O3 and 0.1 to 1.0 parts of CeO2; wherein, the weight percentage of at most one component among Bi2O3, Ag2O and In2O3 is 0.

2. The high-airtightness, low-fog, environmentally friendly cover glass according to claim 1, characterized in that: SiO2 is 53.0-60.0 parts, or 53.0-58.0 parts, or 55.0-58.0 parts, or 56.0-58.0 parts, or 56.5-57.5 parts; Or, Al2O3 is 9.0-9.5 parts, or 11.0-15.0 parts, or 11.0-14.0 parts, or 12.0-14.0 parts, or 12.5-13.5 parts; Or, CaO is 0.4-2.0 parts, or 0.7-2.0 parts, or 0.7-1.3 parts, or 1.7-2.0 parts; Or, MgO is 4.9-8.0 parts, or 5.0-8.0 parts, or 5.0-7.0 parts, or 5.5-6.5 parts; Or, K2O is 3.5-6.5 parts, or 3.5-6.0 parts, or 4.0-6.0 parts, or 4.5-5.5 parts; Or, Na2O is 9.2-15.0 parts, or 9.0-14.0 parts, or 9.0-14.0 parts, or 10.0-12.0 parts, or 11.0-12.0; Or, Li2O is 0.1-2.0 parts, or 0-1.0 parts, or 0-0.9 parts, or 0.1-0.9 parts, or 0.3-0.7 parts; Or, ZrO2 is 0.5-1.3 parts, or 1.3-2.0 parts, or 0.7-1.3 parts; Or, B2O3 is 2.0-5.5 parts, or 2.0-5.0 parts, or 2.0-4.5 parts, or 2.0-4.0 parts, or 2.0-3.5 parts, or 2.5-3.5 parts, or 2.8-3.2 parts; Or, Bi2O3 is 0.1-3.0 parts, or 0.1-2.5 parts, or 0.1-2.0 parts, or 0.1-1.5 parts, or 0.1-1.0 parts, or 0.1-0.9 parts, or 0.3-0.7 parts; Or, Ag2O is 0.1-2.0 parts, or 0.1-1.5 parts, or 0.1-1.0 parts, or 0.1-0.9 parts, or 0.3-0.7 parts; Or, In2O3 is 0.1 to 3.0 parts, or 0.1 to 2.5 parts, or 0.1 to 2.0 parts, or 0.1 to 1.5 parts, or 0.1 to 1.0 parts, or 0.1 to 0.9 parts, or 0.3 to 0.7 parts; Or, CeO2 is 0.1-0.8 parts, or 0.1-0.7 parts, or 0.1-0.6 parts, or 0.1-0.5 parts, or 0.1-0.4 parts, or 0.1-0.3 parts, or 0.3-0.8 parts, or 0.4-0.8 parts, or 0.4-0.7 parts, or 0.5-0.7 parts.

3. The high-airtightness, low-fog, environmentally friendly cover glass according to claim 1, characterized in that Na The weight percentage of K2O is greater than seven-ninths of the weight percentage of K2O; Or, the weight percentage of B2O3 is less than two-thirds of the weight percentage of Al2O3; Or, the sum of the weight parts of Bi2O3, Ag2O, and In2O3 is greater than 1 part, preferably 1.1 to 5 parts, more preferably 1.1 to 4 parts, and even more preferably 1.1 to 2 parts.

4. The high-airtightness, low-fog, environmentally friendly cover glass according to claim 1, characterized in that: Water vapor transmission rate ≤8×10 -9 g / m 2 ·d, preferably (2 to 8)×10 -9 g / m 2 ·d, preferably (2 to 6)×10 -9 g / m 2 ·d, preferably (2 to 5)×10 -9 g / m 2 ·d, preferably (2 to 3)×10 -9 g / m 2 ·d; Or, haze ≤ 0.39%, preferably 0.18-0.39%, preferably 0.18-0.32%, preferably 0.18-0.26%, preferably 0.18-0.24%, preferably 0.18-0.20%, preferably 0.18-0.19%; Or, flexural strength ≥ 129 MPa, preferably 129-141 MPa, preferably 132-141 MPa, preferably 139-141 MPa; Or, the maximum optical transmittance of the 2 mm glass sample in the wavelength range of 400 to 1000 nm is ≥ 90.0%, preferably 90.0 to 91.8%, and preferably 91.0 to 91.8%.

5. A method for preparing the high-airtightness, low-fog, environmentally friendly cover glass according to claim 1, characterized in that: The raw materials are mixed evenly according to the proportion of each component, and then the mixed mixture is melted, stirred, clarified and formed in sequence to obtain the product.

6. The method for preparing the high-airtightness, low-fog, environmentally friendly cover glass according to claim 5, characterized in that: The melting temperature is 1500-1580°C; preferably, the melting time is 8-30h; Or, the stirring speed is 10-20 r / min, and the stirring time is 3-12 h; Alternatively, the molding temperature is 1350-1400° C., and the molding time is 5-25 min.

7. Use of the high-airtightness, low-fog, environmentally friendly cover glass according to any one of claims 1 to 4 in the preparation of a screen substrate.

8. Use of the high-airtightness, low-fog, environmentally friendly cover glass according to any one of claims 1 to 4 in preparing a cover for a digital product.

9. The use according to claim 8, characterized in that: The cover glass comprises a light absorption region, and the maximum optical transmittance of the light absorption region is ≤2.9%, preferably 1.3-2.9%, and preferably 1.3-2.0%.

10. The use according to claim 9, characterized in that: The light absorption zone is obtained by continuing to blacken the high-airtightness, low-fog, environmentally friendly cover glass; preferably, the blackening treatment is carried out in a reducing atmosphere, the blackening treatment time is 4000 to 16000 minutes, the pressure of the reducing atmosphere is 0.01 to 0.5 MPa, and the temperature is 450 to 620°C.

Citation Information

Patent Citations

  • High-aluminum high-sodium cover plate glass

    CN104176929A

  • Formula of glass used to prepare touch screen cover plate

    CN104211301A

  • Alkali-free aluminosilicate glass, composition for same, method for preparing alkali-free aluminosilicate glass and application thereof

    CN105731790A

  • Optical glass, preform and optical element

    CN110267923A

  • Low-haze environment-friendly anti-halation photoelectric glass as well as preparation method and application thereof

    CN118344005A

Cited By

  • Glass-based cover plate material as well as preparation method and application thereof

    CN117756386A

  • A glass-based cover material, its preparation method, and its application.

    CN117756386B